Crecer en Una Granja - Stone, Lynn M. (Vero Beach, Fla. : Rourke Pub., 2002)
Briefly describes what life is like for children living on a farm.
Includes bibliographical references (p. 24).
Keywords: Farm life -- Juvenile literature. -- North America